The 1866 Cholera Scare: Implications for Canadian State-Making and Current Pandemic Management - Rucchetto, Anne (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2021)
The cholera scare of 1866 had significant implications for Canadian state-making, public health, and notions of social welfare. Shared action by policymakers, police, and public health authorities led to an unprecedented prevention campaign that included moralistic and punitive elements. This paper will outline the ways that the 1866 cholera scare served to develop the foundations of power consolidation, social control, and surveillance practices used in Canada today.